Bulk electronic structure of high-order quaternary approximants - Shuvam Sarkar; Pampa Sadhukhan; Vipin Kumar Singh; Andrei Gloskovskii; Kazuhiko Deguchi; Nobuhisa Fujita; Sudipta Roy Barman (Physical Review Research, 2021)
The bulk electronic structures of two high-order quaternary approximants of F-type icosahedral (i)-Al-Pd-TM quasicrystal: Al-Pd-Cr-Fe and Al-Pd-Mo-Fe, having similar electron to atom (e/a) ratio as i-Al-Pd-Mn quasicrystal, have been investigated by hard x-ray photoelectron spectroscopy. We establish the presence of a well-formed pseudogap at the Fermi level in both the approximants. The pseudogap turns out to be deeper in the approximants compared to i-Al-Pd-Mn, and this is supported by specific heat data. Modifications in the line shape of Al 2s core-level main peak as well as the plasmon loss peaks indicate enhanced hybridization of Al sp and transition metal d states in the approximants, which could be one of the possible reasons for their pseudogap. The absence of magnetic exchange splitting in the Fe 2p core-level spectra establishes the nonmagnetic nature of the approximants.